2017
DOI: 10.3390/app7070680
|View full text |Cite
|
Sign up to set email alerts
|

Robust Co-Optimization to Energy and Reserve Joint Dispatch Considering Wind Power Generation and Zonal Reserve Constraints in Real-Time Electricity Markets

Abstract: This paper proposes an energy and reserve joint dispatch model based on a robust optimization approach in real-time electricity markets, considering wind power generation uncertainties as well as zonal reserve constraints under both normal and N-1 contingency conditions. In the proposed model, the operating reserves are classified as regulating reserve and spinning reserve according to the response performance. More specifically, the regulating reserve is usually utilized to reduce the gap due to forecasting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The managers and decision makers must identify and fix or remove the bottlenecks; that is a vital and critical issue for manufacturing supply chain processing system. For example, with using wind power generation in electricity markets, there is a bottleneck in zonal placement of spinning reserve that inhibits the deliverability of reserve that solves the increasing total cost by co-optimization model [33]. The bottleneck can be in sparking communication when there is an increase in consensus nodes that can cause problems for the large-scale applications and may increase the cost of communication.…”
Section: The Challenge Of Supply Chain Bottlenecksmentioning
confidence: 99%
“…The managers and decision makers must identify and fix or remove the bottlenecks; that is a vital and critical issue for manufacturing supply chain processing system. For example, with using wind power generation in electricity markets, there is a bottleneck in zonal placement of spinning reserve that inhibits the deliverability of reserve that solves the increasing total cost by co-optimization model [33]. The bottleneck can be in sparking communication when there is an increase in consensus nodes that can cause problems for the large-scale applications and may increase the cost of communication.…”
Section: The Challenge Of Supply Chain Bottlenecksmentioning
confidence: 99%
“…As mentioned above, the Greek interconnected power system has been examined. Details on its characteristics are provided in recent papers [13][14][15][16]. In Greece, the Public Power Corporation (PPC) has a dominant position with about 80% of the retail market at the end of the year 2018.…”
Section: Resultsmentioning
confidence: 99%
“…Market reforms also considered techno-economic characteristics of the power system. Li et al [14] identified the need for technical constraints towards a robust co-optimization of energy and reserves in real-time electricity markets Market reform might also include the adoption of other market algorithms for the clearing of the day-ahead market. Koltsaklis and Dagoumas [15] examined the adoption of the Pan-European Hybrid Electricity Market Integration Algorithm (EUPHEMIA) in the Greek electricity market, aiming to quantify the effects of different order types as well as of the strategy of a market participant with the dominant position.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve the goal of poverty alleviation in rural areas by 2020, China implements the strategy of supporting the poor in rural areas of western China. Since renewable energy is uncertain, robust optimal scheduling algorithms [17,18] are usually applied to cope with this issue. To accommodate more renewable energy sources, flexibility from the power load is frequently adopted [19,20].…”
Section: Introductionmentioning
confidence: 99%